2021
DOI: 10.1088/1674-1056/ac01c4
|View full text |Cite
|
Sign up to set email alerts
|

Insight into influence of thermodynamic coefficients on transient negative capacitance in Zr-doped HfO2 ferroelectric capacitors*

Abstract: We study the influence of the thermodynamic coefficients on transient negative capacitance for the Zr-doped HfO2 (HZO) ferroelectric capacitors by the theoretical simulation based on the Landau–Khalatnikov (L-K) theory and experimental measurement of electrical properties in the resistor-ferroelectric capacitor (R-FEC) circuit. Our results show that the thermodynamic coefficients α, β and γ also play a key role for the transient NC effect besides the viscosity coefficient and series resistor. Moreover, the sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…However, carbon contaminants are unavoidable in HZO films during the ALD process, which have a negative effect on the formation of the o-phase. The sputtering technique is an effective method for preparing HZO due to its low cost and flexible deposition conditions . It was found that the best doping concentration of ferroelectric properties in the Hf X Zr 1– X O 2 system is X = 0.5 …”
Section: Introductionmentioning
confidence: 99%
“…However, carbon contaminants are unavoidable in HZO films during the ALD process, which have a negative effect on the formation of the o-phase. The sputtering technique is an effective method for preparing HZO due to its low cost and flexible deposition conditions . It was found that the best doping concentration of ferroelectric properties in the Hf X Zr 1– X O 2 system is X = 0.5 …”
Section: Introductionmentioning
confidence: 99%